Mechanical Design of an Integrated Car Swivel Seat with Special Wheelchair for Disabled Drivers and Passengers - LEOW CHUN HANG; MOHD AZWIR AZLAN; AHMAD FA'UD BIN IDRIS (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This project presents the design of an integrated car swivel seat with a special wheelchair to improve accessibility for disabled drivers and passengers. Current systems often require assistance and lack smooth integration, limiting independence. The objective is to develop a functional, ergonomic, and safe mechanism suitable for hatchbacks and sedans. The design process followed George E. Dieter’s engineering method, including literature review, patent study, benchmarking, and SolidWorks simulation. Survey data and car measurements guided the final concept. The outcome is a rotating, sliding seat system integrated with a compatible wheelchair base, offering improved ease of transfer and user safety. This solution enhances mobility and provides a foundation for future development.